2021
DOI: 10.3390/ijerph18094942
|View full text |Cite
|
Sign up to set email alerts
|

Body Mapping in a Drug and Alcohol Treatment Program: Eliciting New Identity and Experience

Abstract: Arts-based approaches have not been widely used in the drug and alcohol treatment sector. In this study, we examined the utility of the arts-based method of Body Mapping in an Australian residential treatment centre. Two workshops were held to explore young people’s strengths and support networks in order to improve understandings of young people’s lives, identities and experiences of treatment. Semi-structured follow-up interviews were conducted and triangulated with observational notes and staff interviews. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Fraser and al Sayah, 11 who found that visual methods, such as photos and Body Mapping, were the most used ABM. 2…”
Section: Arts-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fraser and al Sayah, 11 who found that visual methods, such as photos and Body Mapping, were the most used ABM. 2…”
Section: Arts-based Methodsmentioning
confidence: 99%
“…The study of Macken et al 2 aimed to explore the use of Body Mapping as a research method with young people in residential treatment for drug and alcohol issues and to examine how Body Mapping can engage young people in exploring their strengths and sources of support during treatment. They found that Body Mapping produced richer data and accessed new narratives not usually captured in more traditional interviews, in a subsequent interview where young people explained their Body Map.…”
Section: (19%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen women participated in a body-mapping session and completed a follow-up telephone interview. Sample sizes of 6–12 participants have been recommended for body-mapping research to capture rich data relevant to research questions and a range of experiences (Macken et al, 2021). Body-mapping participants were aged 19–39, with a mean age of 25.5 years; 68.8% identified as heterosexual, 31.2% identified as bisexual, and most were partnered (68.8%).…”
Section: Methodsmentioning
confidence: 99%
“…The methodological article by Macken and her colleagues [ 11 ] explores the utility of using body mapping, an arts-based method, in the drug and alcohol treatment sector in Sydney, Australia, to explore young people’s strengths and support networks. They found body mapping facilitated discussions on subject matter normally challenging for young people to talk about.…”
Section: The Special Issuementioning
confidence: 99%